2020
DOI: 10.1371/journal.pone.0227926
|View full text |Cite
|
Sign up to set email alerts
|

CNP mediated selective toxicity on melanoma cells is accompanied by mitochondrial dysfunction

Abstract: Cerium (Ce) oxide nanoparticles (CNP; nanoceria) are reported to have cytotoxic effects on certain cancerous cell lines, while at the same concentration they show no cytotoxicity on normal (healthy) cells. Redox-active CNP exhibit both selective prooxidative as well as antioxidative properties. The former is proposed to be responsible for impairment of tumor growth and invasion and the latter for rescuing normal cells from reactive oxygen species (ROS)-induced damage. Here we address possible underlying mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 87 publications
2
30
0
Order By: Relevance
“…Since the cellular uptake of GP is similar in both A375 melanoma cells and NHEM melanocytes, the question rises why GP has a selective toxic effect on tumor cells. One explanation could be oxidative stress, since tumor cells have an increased basal ROS content compared to healthy cells and are, therefore, more susceptible to further ROS formation via, for example, nanoparticles or H 2 O 2 (Alili et al 2013 ; Aplak et al 2020 ). It has been reported that GP has a pro-oxidative effect in breast, pancreatic and prostate cancer (Zubair et al 2016 ) as well as in multiple myeloma (Xu et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the cellular uptake of GP is similar in both A375 melanoma cells and NHEM melanocytes, the question rises why GP has a selective toxic effect on tumor cells. One explanation could be oxidative stress, since tumor cells have an increased basal ROS content compared to healthy cells and are, therefore, more susceptible to further ROS formation via, for example, nanoparticles or H 2 O 2 (Alili et al 2013 ; Aplak et al 2020 ). It has been reported that GP has a pro-oxidative effect in breast, pancreatic and prostate cancer (Zubair et al 2016 ) as well as in multiple myeloma (Xu et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“… 38 Cerium oxide nanoparticles (CNP; nanoceria) have been reported to induce changes in dynamics that lead to mitochondrial dysfunction and eventually lead to melanoma cell death. 39 Soares et al demonstrated that increased MFN2 expression in melanoma is significantly positively correlated with lymph node involvement and distant metastasis. 40 In this study, we found that JQ1 treatment significantly increased the expression of mitochondrial fission proteins and decreased the expression of fusion proteins in B16 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, there is limited information regarding the role of mitochondrial dynamics in tumor progression and its effect on mitochondrial dysfunction 38 . Cerium oxide nanoparticles (CNP; nanoceria) have been reported to induce changes in dynamics that lead to mitochondrial dysfunction and eventually lead to melanoma cell death 39 . Soares et al demonstrated that increased MFN2 expression in melanoma is significantly positively correlated with lymph node involvement and distant metastasis 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The former mechanism is engaged by cerium (Ce) oxide nanoparticles (CNP; nanoceria) which selectively kills A375 melanoma cells through the increase of ROS concentration, prevalently hydrogen peroxide, at mitochondrial level. Such event occurs concomitantly to mitochondrial thiol oxidation and is followed by modifications in mitochondrial bioenergetics, dynamics, and cristae morphology, and ultimately by mitochondrial dysfunction-induced cell death [ 173 ]. Moreover, increased concentrations of ROS can reduce melanoma development through activation of cell cycle regulators and arrest of cell cycle in G2/M phase by the inhibition of Cdc25c and cyclin A [ 171 ].…”
Section: Introductionmentioning
confidence: 99%